Marcelismo e ruptura democrática no contexto da transformação social portuguesa dos anos 1960 e 1970 - Loff, Manuel (2007)
Reading the 1950’s and, mostly, the 1960’s as an historical cycle of structural and speedy change in Portuguese society, a time of real industrial revolution together with rural exodus, massive emigration and growing politicization as consequence of the Colonial War (1961-74), Marcelism emerges as the last chance of the Portuguese dictatorship to control a modernization and massification process which had become clearly inevitable. The interpretation I am proposing does not perceive Marcelism as an autonomous object of analysis, but integrates it in a period running from the 1958-62 crisis of Salazarism until the final breakdown, in 1974, of the regime. This may be read as an historical cycle of fast (although it can be perceived as slow as far as the political events are concerned) materialization of the social and economic change which provided, in 1974, the inexorableness of the democratic rupture. In other words, I am not proposing to underline Marcelism’s role in recent Portuguese History as an impulse for change, but merely as a transitional period, clearly assimilated in a wider period which, from my point of view, began in 1958, ten years before Caetano got back to power, the moment in which, in fact, Salazar interrupted his short political experience as heir-to-be of the dictator.